Penerapan Sistem Manufaktur Terintegrasi dalam Meningkatkan Produktivitas UKM melalui Pendekatan Rekayasa Industri - Zulfadlillah Zulfadlillah (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2024)
SMEs play a strategic role in the national economy but face significant challenges in improving productivity and competitiveness in an increasingly dynamic market environment. This research analyzes the implementation of integrated manufacturing systems in SMEs through an industrial engineering approach. Using a qualitative methodology, data was collected through a hybrid webinar platform involving 45 participants from SME sectors, academia, industry, and local government. The research identifies critical success factors for implementation, including management commitment, financial resources, and continuous human resource training, which collectively contribute 68% to successful technology adoption. The PDCA-based technical assistance model developed shows a 30% increase in operator productivity through lean manufacturing implementation and production layout optimization. Economic impacts include an average 40% increase in SME turnover within six months post-implementation, while social benefits include a 12% reduction in local unemployment. The study confirms that integrated manufacturing systems effectively improve SME productivity by 15-25%, though challenges remain in digital infrastructure limitations and resistance to traditional work system changes, requiring multi-stakeholder collaboration to develop a comprehensive supporting ecosystem.